The Lithology Spatial Distribution of South Jableh Plain Using Spatial Statistical Methods - عبد الرحمن عباس; الأسعد علي; خضور ريم (Latakia University Journal -Engineering Sciences Series, 2020)
The idea of ​​ spatial interpolation stands of great importance depending on the accuracy of estimated (Hydrogeological) parameters of this area, which reduces excessive efforts to reach the best Hydrogeological model of the region with as little as possible, thus reducing the overall cost of the project. The studied area is located within the Sin plain (the southern part of the JABLEH plain). A free layer of water, ranging between 1m and 30m in thickness. The study relied on groundwater level data, soil thickness and type in 339 wells. The importance of this research Lies in mapping the best spatial distribution of characteristics using spatial statistical methods The aim of the research is to estimate the Coefficient of Permeability of the aquifer layer and its effective thickness using the two methods of spatial statistics methods (Kriging and IDW) for Hydrogeological parameters in the southern part of the Jableh plain.